Proposed new interior design of Ruby Pets Clinic for Ruby Anandan Sdn. Bhd. at No. 22, Jln Jati 3/6, Seksyen 3, 40000 Shah Alam, Selangor / Khairah Filzah Aman - Aman, Khairah Filzah (Faculty of Architecture, Planning and Surveying, 2011)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design of Ruby Pets Clinic for Ruby Anandan Sdn Bhd at No.22, Jin Jati 3/6, Section 3, 40000 Shah Alam, Selangor. This project is for make the new image and complete a client needed. This proposal is to open new concept of Ruby Pets Clinic with modern nature images. The main objective is to introduce a ‘Perceive by touching’ concept to follow the client need besides suitable with company corporate image and identify. The idea to undertake this project was given due attention after taking into consideration the current and design issues, and to solve the problems encountered by the Pets Clinic efficiently. Therefore, a plan was proposed to prepare new design and approach that may interest and fulfil the aspiration of the client, workers and customer. Design concept should be taken into account as profoundest study. From the research and observation conducted, all data and details gathered was used as a guideline in the design process.